Growth Kinetics of Lactobacillus plantarum and Lactobacillus sp. in MRS Medium - Yoyok B Pramono; Eni Harmayani; Tyas Utami (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2003)
Lactobacillus plantarum FNCC 250 and Lactobacillus sp. FNCC 401 were isolated from traditional fermented food which had potential properties as probiotic agents and to reduce cholesterol. The aim of the research was to study the growth kinetics of Lactobacillus plantarum FNCC 250 and Lactobacillus sp. FNCC 401 at MRS medium, using glucose a substrate limiting factor. Cells were inoculated into MRS medium containing glucose concentration of 0.05 ; 0.1 ; 0.2 ; 0.3 ; 0.5 ; 1 ; 1.5 ; 2 ; and 3 % (w/v). Fermentation was carried out at 37oC, with initial pH 6.8 and was monitored for 24 hours. During the fermentation, dry cell weight, reducing sugar and pH were analysed. The results showed that Ks ( the substrate saturation constant) of Lactobacillus plantarum FNCC 250 was 0.04 (g.l-1) ; ì max (the maximum growth rate) was 0.17 (h-1) ; and Y (growth yield) was 0.24 ( g.g-1), meanwhile for Lactobacillus sp. FNCC 401 Ks was 0.06 (g.l-1), ì max was 0.26 (h -1) ; and Y (growth yield) was 0.24 ( g.g -1). Key words : Fermentation, growth kinetics, Lactobacillus plantarum, and Lactobacillus sp.